Thermal profile and microstructure of wrought aluminium 7075 for semisolid metal processing - Nur Azhani, Abd Razak; Asnul Hadi, Ahmad; Mohd Rashidi, Maarof (Universiti Malaysia Pahang, 2020)
Thermal analysis (TA) is a non-damaging and quick method to check the molten metal’s condition preceding to casting. This paper aims to present the relationship between fraction solid and temperature by utilising cooling curve analysis (CCA), to acquire correct processing parameters for wrought aluminium 7075 in semisolid condition. An induction furnace was used to heat a graphite crucible containing wrought aluminium 7075 alloy up to the temperature of 750 °C. A calibrated Chromel-Alumel K-type thermocouple was placed at the centre of the crucible and was submerged to 15 mm in the melt. The solidification temperature and time were measured by Data Logger GL-220. Normal, intermediate, and high cooling rate conditions were achieved when the crucible was left in an open atmosphere, in an open atmosphere with additional minimum airflow, and in an open atmosphere with the maximum airflow, respectively. It was found that the normal cooling rate was estimated at 2.23 °C/s, the intermediate cooling rate was calculated at 2.88 °C/s while the high cooling rate was recorded at 3.20 °C/s. The increase in cooling rate conditions has a significant effect on the changes of phases during solidification process where it leads to the decreased in liquidus, eutectic and solidus temperature. The microstructure feature was found to have a significant difference with the variation of cooling rates where higher cooling rate led to smaller primary grain size.